Induction of micronuclei and nuclear abnormalities in tadpoles of the common toad (Rhinella arenarum) treated with the herbicides Liberty® and glufosinate-ammonium - Lajmanovich, Rafael Carlos (2014)
The assessment of micronucleated erythrocytes (ME) in blood represents a widely used method for thedetection of chromosomal damage by chemical agents, such as herbicides that may occur as water con-taminants. We investigated the changes in some circulating blood-cell parameters of tadpoles of thecommon toad (Rhinella arenarum) that were exposed during 48 or 96 h to three sub-lethal concentra-tions (3.75, 7.5, and 15 mg/L) of a commercial formulation of a glufosinate-ammonium (GLA)-basedherbicide (Liberty®, LY®) as well as to the corresponding active ingredient GLA. The frequency of MEand other erythrocyte nuclear abnormalities (ENA, i.e., lobed nuclei, binucleates or segmented nuclei,kidney-shaped nuclei, notched nuclei, and picnotic nuclei) were evaluated and compared with positive(cyclophosphamide, CP, 40 mg/L) and negative (de-chlorinated tap water) controls. The results indicatethat the exposure of R. arenarum tadpoles to LY®induces a concentration-dependent increase in ME fre-quency. The ENA frequency at 48 h was also significantly higher than that in the negative control groupfor all the chemicals assayed (CP, LY®and GLA) whereas at 96 h, increases in ENA over the negative controlgroup were found only for CP and GLA (7.5 mg/L). Our study demonstrates that the commercial formula-tion of a GLA-based herbicide induces micronucleus formation in R. arenarum tadpoles, in contrast to theactive ingredient. According to these results, the inert ingredients of the commercial formulation playedan important role in the production of genotoxic damage in erythrocytes of amphibian tadpoles.